The influence of immortal time bias in observational studies examining associations of antifibrotic therapy with survival in idiopathic pulmonary fibrosis: A simulation study - Zheng, Qiang; Otahal, Petr; Cox, Ingrid A.; de Graaff, Barbara; Campbell, Julie A.; Ahmad, Hasnat; Walters, E. Haydn; Palmer, Andrew J. (Frontiers in Medicine, 2023)
Background Immortal time bias (ITB) has been overlooked in idiopathic pulmonary fibrosis (IPF). We aimed to identify the presence of ITB in observational studies examining associations between antifibrotic therapy and survival in patients with IPF and illustrate how ITB may affect effect size estimates of those associations. Methods Immortal time bias was identified in observational studies using the ITB Study Assessment Checklist. We used a simulation study to illustrate how ITB may affect effect size estimates of antifibrotic therapy on survival in patients with IPF based on four statistical techniques including time-fixed, exclusion, time-dependent and landmark methods. Results Of the 16 included IPF studies, ITB was detected in 14 studies, while there were insufficient data for assessment in two others. Our simulation study showed that use of time–fixed [hazard ratio (HR) 0.55, 95% confidence interval (CI) 0.47–0.64] and exclusion methods (HR 0.79, 95% CI 0.67–0.92) overestimated the effectiveness of antifibrotic therapy on survival in simulated subjects with IPF, in comparison of the time–dependent method (HR 0.93, 95% CI 0.79–1.09). The influence of ITB was mitigated using the 1 year landmark method (HR 0.69, 95% CI 0.58–0.81), compared to the time–fixed method. Conclusion The effectiveness of antifibrotic therapy on survival in IPF can be overestimated in observational studies, if ITB is mishandled. This study adds to the evidence for addressing the influence of ITB in IPF and provides several recommendations to minimize ITB. Identifying the presence of ITB should be routinely considered in future IPF studies, with the time–dependent method being an optimal approach to minimize ITB.